2018
DOI: 10.3389/fnhum.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Distinctions: How Attentional Templates Influence EEG Parameters of Cognitive Control in a Spatial Cuing Paradigm

Abstract: Using event-related potentials (ERPs) of the electroencephalogram, we investigated how cognitive control is altered by the scope of an attentional template currently activated in visual working memory. Participants performed a spatial cuing task where an irrelevant color singleton cue was presented prior to a target array. Blockwise, the target was either a red circle or a gray square and had to be searched within homogenous (gray circles) or heterogeneous non-targets (differently colored circles or various sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
(124 reference statements)
0
7
1
Order By: Relevance
“…On the one hand, our conclusion that the CP changes as a function of search task is consistent with some observations from previous studies. For instance, the CP was unaffected by the match between cue and target when the target was easy to find (Mertes et al, 2016), whereas the CP was larger for matching than nonmatching cues when the target was more difficult to find (Schönhammer et al, 2016(Schönhammer et al, , 2020Mertes & Schneider, 2018). On the other hand, our conclusions are at odds with the previous interpretation that the CP reflects cue suppression (Harris et al, 2019;Mertes & Schneider, 2018;Mertes et al, 2016;Sawaki & Luck, 2013).…”
Section: Relation To Previous Interpretations Of the Cpcontrasting
confidence: 99%
See 2 more Smart Citations
“…On the one hand, our conclusion that the CP changes as a function of search task is consistent with some observations from previous studies. For instance, the CP was unaffected by the match between cue and target when the target was easy to find (Mertes et al, 2016), whereas the CP was larger for matching than nonmatching cues when the target was more difficult to find (Schönhammer et al, 2016(Schönhammer et al, , 2020Mertes & Schneider, 2018). On the other hand, our conclusions are at odds with the previous interpretation that the CP reflects cue suppression (Harris et al, 2019;Mertes & Schneider, 2018;Mertes et al, 2016;Sawaki & Luck, 2013).…”
Section: Relation To Previous Interpretations Of the Cpcontrasting
confidence: 99%
“…With fixed target color, only cues in the target color captured attention, whereas unrelated cue colors did not. Thus, the precision of the attentional template was better than expected on the basis of singleton search alone (see also Harris, Jacoby, Remington, Travis, & Mattingley, 2019;Mertes & Schneider, 2018;Harris, Becker, & Remington, 2015;Eimer & Kiss, 2010). In contrast, precise attentional templates are required when the target is shown with a nontarget in a different color and it is no longer possible to search for a singleton (Kerzel & Witzel, 2019;Grubert & Eimer, 2016;Irons et al, 2012;Ansorge, Horstmann, & Carbone, 2005).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, in a later time window, we obtained a large lateralized positivity after the N2pc, and only for those cues that produced a significant N2pc (i.e., relatively matching critical cues or context cues). The first studies attributed these positives to the suppression of a selected item after attentional capture, possibly reflecting disengagement of attention from the cue location (Mertes & Schneider, 2018; Mertes et al, 2016; Sawaki & Luck, 2013). In subsequent research, the time interval between cue and target array was varied, and it was found that the positivity is time-locked to the target array and is therefore unrelated to attentional capture by the cue.…”
Section: Discussionmentioning
confidence: 99%
“…The event-related potential (ERP) technique has been used to investigate attentional capture as well as suppression by task-irrelevant stimuli, indexed by N2-posteriorcontralateral (N2pc) and distractor positivity (P D ), respectively (Hickey et al, 2009;Luck & Hillyard, 1994a, 1994b. N2pc, usually appearing 180-280 ms after stimuli onset, is the difference wave between ERPs elicited at the contralateral and ipsilateral electrodes, with its maximal amplitude at the PO7/PO8 electrode (Corriveau et al, 2012;Dell'Acqua et al, 2006;Luck & Hillyard, 1994a, 1994b.…”
Section: Introductionmentioning
confidence: 99%